Impact of Soil and Water Conservation on Household Income in East Shoa Zone of Oromia - Bati, Beriso; Esmael, Yasin (Journal of Food Industry, 2024)
This study was conducted to assess the impact of Soil and Water Conservation (SWC) intervention on the livelihood of smallholder farm households in terms household income and productivity. To meet this objective primary data was gathered in 2010 from 120 sample respondents (50 SWC program participants and 70 non-participants). Descriptive and inferential statistics (Logistic regression) and propensity score matching (PSM) models were used to address the stated objectives. The analysis of mean difference in outcome variables before matching result indicated that the mean total crop yield for SWC practiced respondent households is 29.10 and 27.80 quintal/ha having 1.30 quintal difference in the study. In the meantime total annual crop income of households who participated in SWC program was 33,903 and 33,808.40 birr. Except sex of the household, Market information, amount of land cultivated, Education and farm experience influenced the probability of HH participation in SWC positively and significantly at 10% expect land cultivated at 5% level. Nominal results of analysis of treatment effects indicate that there was a sign of positive impact on both of the variables considered due to SWC program. However, the changes in crop productivity and gross household income could not be statistically justified as there was no statistically significant difference between the two groups in terms of these variables. The possible reason could be that SWC programs are not short-term nature and impacts are to be realized gradually with increased adoption and intensification of activities.